Alleghanian deformation of Cambrian metasedimentary rocks on Avalonia in south-central Rhode Island, USA - Carter, Matthew J.; Mosher, Sharon (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2013)
Lower greenschist-facies metasedimentary rocks of the Middle Cambrian Conanicut Group occur in and around Beavertail State Park, Rhode Island. Detailed structural mapping (1:1000-scale) and petrology of these rocks indicate an early fold generation (F1) and axial planar metamorphic foliation (S1). F1 is folded by a more prominent, E-verging, NNE- to NNW-trending, non-coaxial fold generation (F2) and an associated pressure solution-enhanced crenulation cleavage (S2). A third map-scale fold generation is inferred from NNE-trending broad folding of F2 and S2. N-S extension resulted in boudins that deformed S2 on a scale of 1–10 m, whereas late planar quartz veins indicate NW-SE extension. All structures are cross cut by faults striking N- to NE- and ENE-to ESE that show dominantly normal motion with minor sinistral or dextral components. Kink bands associated with faulting trend NNE to ENE with WNW to NNW side up. The vertical Beaverhead shear zone juxtaposes the Cambrian rocks with Pennsylvanian rocks of the Narragansett Basin, and deflects S2 in a dextral sense, consistent with motion recorded elsewhere.The Cambrian rocks record the same deformation and metamorphism as the adjacent Narragansett Basin rocks. No evidence was found for pre-Alleghanian deformation or for northwest- or north-directed thrusting and accretion of a Meguma-like terrane during the Alleghanian orogeny. If the Beaverhead shear zone was a preexisting terrane boundary within Avalonia, both the Cambrian and Pennsylvanian Narragansett Basin sediments were deposited aﬅer terrane accretion.RÉSUMÉDes roches profondes métasédimentaires du faciès des schistes verts, que l’on retrouve dans le groupe Conanicut du Cambrien moyen, sont présentes dans le Beavertail State Park, au Rhode Island, et dans les environs. Une cartographie structurale détaillée (à l’échelle 1:1 000) et la pétrologie de ces roches indiquent la formation précoce d’un pli (F1) et une foliation métamorphique (S1) de plan axial. Le F1 est causé par la formation d’un pli (F2) non coaxial plus dominant, à vergence est et d’orientation NNE-NNO ainsi que par une schistosité de crénulation (S2) amplifiée en raison d’une dissolution par pression connexe. La formation d’un troisième pli à l’échelle cartographique est provoquée par un vaste plissement du F2 et de la S2 d’orientation NNE. Une extension N-S a produit des boudins qui déforment la S2 sur l’échelle de 1 à 10 m, tandis que des veines de quartz planes formées ultérieurement indiquent une extension NO-SE. Toutes les structures sont traversées par des failles orientées N-NE et ENE-ESE montrant un mouvement normal dominant accompagné de composantes senestres et dextres peu importantes. Les bandes froissées associées à ces failles sont orientées NNE-ENE et présentent une tangente verticale ONO-NNO. Dans la zone de cisaillement verticale de Beaverhead, les roches du Cambrien sont juxtaposées aux roches de la Pennsylvanie du bassin Narragansett, et la S2 dévie en un mouvement dextre, ce qui concorde avec le mouvement enregistré ailleurs.Les roches du Cambrien montrent la même déformation et le même métamorphisme que les roches du bassin Narragansett adjacent. On n’a trouvé aucune donnée appuyant la création d’une déformation avant l’orogenèse alléghanienne ni celle d’un chevauchement et d’une accrétion orientés vers le nord ou le nordouest d’un terrane semblable à la zone de Meguma lors de l’orogenèse alléghanienne. Si la zone de cisaillement verticale de Beaverhead constituait une limite de terrane qui existait avant l’orogenèse de l’Avalonien, les sédiments cambriens et pennsylvaniens du bassin Narragansett se sont déposés après l’accrétion du terrane.[Traduit par la redaction]